PENGARUH PENDIDIKAN TERHADAP KINERJA KARYAWAN BAITUL MAL WAT-TAMWIL DI PROVINSI RIAU - KHORNELIS DEHOTMAN (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
The theme of the article is based on economic principles of Islam. This study aims to identify and analyze whether the educational effect on the performance of Baitul Mal wat-Tamwil (BMT) as an Islamic Micro Finance Institutions (LKMS) in Riau Province. Research is the study of literature. The results showed that the BMT in Riau faced on human resources, one of which is the education of human resources also faced BMT activists across Indonesia. The role of education in improving the quality of human resources is of utmost importance, considering that education is the way out of the problems faced from congestion knowledge and skills of a person in the field of work. Someone learned on the job, looking for solutions to the problems encountered, able to master the feeling when facing an angry person to person encounters, all of it is the contribution of the role of education. Meanwhile education followed by BMT employees were able to be driving in the future by way of addressing the well and in accordance with syar'i.